Strongly anomalous non-thermal fixed point in a quenched two-dimensional Bose gas - Karl, Markus; Gasenzer, Thomas (New journal of physics, 2017)
Universal scaling behavior in the relaxation dynamics of an isolated two-dimensional Bose gas is studied by means of semi-classical stochastic simulations of the Gross-Pitaevskii model. The system is quenched far out of equilibrium by imprinting vortex defects into an otherwise phase-coherent condensate. A strongly anomalous non-thermal fixed point is identified, associated with a slowed decay of the defects in the case that the dissipative coupling to the thermal background noise is suppressed. At this fixed point, a large anomalous exponent ##IMG## [http://ej.iop.org/images/1367-2630/19/9/093014/njpaa7eebieqn1.gif] $η \simeq -3$ and, related to this, a large dynamical exponent ##IMG## [http://ej.iop.org/images/1367-2630/19/9/093014/njpaa7eebieqn2.gif] $z\simeq 5$ are identified. The corresponding power-law decay is found to be consistent with three-vortex-collision induced loss. The article discusses these aspects of non-thermal fixed points in the context of phase-ordering kinetics and coarsening dynamics, thus relating phenomenological and analytical approaches to classifying far-from-equilibrium scaling dynamics with each other. In particular, a close connection between the anomalous scaling exponent η , introduced in a quantum-field theoretic approach, and conservation-law induced scaling in classical phase-ordering kinetics is revealed. Moreover, the relation to superfluid turbulence as well as to driven stationary systems is discussed.
Published 20 September 2017
Gesehen am 27.06.2018